2020
DOI: 10.1111/all.14523
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies in serum of convalescent patients following mild COVID‐19 do not always prevent virus‐receptor binding

Abstract: The blood proteomic signature of early-onset pediatric atopic dermatitis shows systemic inflammation and is distinct from adult long-standing disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
68
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(75 citation statements)
references
References 9 publications
6
68
0
1
Order By: Relevance
“…We found that 63.5% of asymptomatic individuals only elicited low levels of neutralizing, and the rest did not produce neutralizing antibodies at all. In addition, 11.8% mild patients also did not produce neutralizing antibody, in line with other reports 18,33,34 . In particular, we demonstrated that neutralizing antibody in asymptomatic individuals decreased rapidly and disappeared in a short time, which indicate that the effectiveness of antibody‐mediated immunity could not be used to guarantee the accuracy of an “immunity passport” or “risk‐free certificate.” Our findings might suggest the risks of “shield immunity” and notably, that asymptomatic individuals might still need immunization with vaccines.…”
Section: Discussionsupporting
confidence: 89%
“…We found that 63.5% of asymptomatic individuals only elicited low levels of neutralizing, and the rest did not produce neutralizing antibodies at all. In addition, 11.8% mild patients also did not produce neutralizing antibody, in line with other reports 18,33,34 . In particular, we demonstrated that neutralizing antibody in asymptomatic individuals decreased rapidly and disappeared in a short time, which indicate that the effectiveness of antibody‐mediated immunity could not be used to guarantee the accuracy of an “immunity passport” or “risk‐free certificate.” Our findings might suggest the risks of “shield immunity” and notably, that asymptomatic individuals might still need immunization with vaccines.…”
Section: Discussionsupporting
confidence: 89%
“…The fact that more than 25% of the convalescent patients did not mount a relevant anti‐RBD antibody response fits to our earlier finding that up to 50% of convalescent patients do not mount antibodies which can inhibit the docking of the virus via RBD to its receptor, ACE2 9 . Also in this study, we found that ~50%‐60% of COVID‐19 convalescent patients have antibodies inhibiting the binding of RBD to ACE2 and hence may be considered to have neutralizing capacity, which confirmed the findings of our last study 9 (data not shown).…”
Section: Discussionsupporting
confidence: 86%
“…Shortly thereafter, it was shown that the disease was caused by a novel beta coronavirus (CoV) subsequently called SARS‐CoV‐2, 4 and the respiratory disease caused by this virus was named COVID‐19 5,6 . Similar to SARS‐CoV, SARS‐CoV‐2 binds with the receptor‐binding domain (RBD) of its spike (S) protein to and enters the target cells via the angiotensin converting enzyme 2 (ACE2) receptor; 7‐9 however, alternative receptors for cell entry such as CD147/EMMPRIN/Basigin 10 and CD299 (formerly CD209L) may exist 11,12 . SARS‐CoV‐2 is highly infectious and is easily spread by aerosols 13,14 …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it should be noted that another possibility that out assay does not test is neutralization antibodies that are not directed against RBD. Thus, our neutralization method similar to other approaches 28,29 add a great diagnostic value. Finally, our cytokine profiling analysis could not define a clear correlation between antibodies response in severe patients and proinflammatory cytokines as IL-1β, IL-6, IL-8 and TNF-α.…”
Section: Discussionmentioning
confidence: 77%